Intratympanic Steroid Use for Sudden Sensorineural Hearing Loss: Current Otolaryngology Practice. (June 2019) - Lechner, Matt; Sutton, Liam; Ferguson, Mark; Abbas, Yasmin; Sandhu, Jaswinder; Shaida, Azhar
Objective: To investigate the current practice of intratympanic steroid (ITS) injection for sudden sensorineural hearing loss (SSNHL) in the United Kingdom and link the data with data from the United States and continental Europe. Methods: A survey of 21 questions was distributed to members of the British Society of Otology using an online survey platform via ENT UK. Data obtained from UK otolaryngologists (n = 171) were integrated with previously published data from other countries, including the United States (n = 63) and continental Europe (n = 908). Results: In the United Kingdom, 62% of responding otolaryngologists use ITS injection for SSNHL, while 38% do not. Of those using ITS, 59% use it as first-line treatment, either using it in conjunction with oral steroids (51%) or using it as monotherapy (8%). Of those that use ITS, a majority (83%) use it as salvage therapy when primary treatment with systemic steroids has failed, and similar results are found in the continental Europe and US surveys. The most commonly used preparation is dexamethasone. Responses to questions regarding treatment regimes used are enlightening and show considerable variation in the treatment regimes used within and between countries. Conclusions: There is a wide variation in practice with regards to ITS for SSNHL hearing loss in the United Kingdom, United States, and continental Europe. In the absence of protocols or definitive guidance from published literature, knowledge of contemporary practice may help guide or encourage reevaluation of clinical practice and will help guide the design of future clinical trials.